EFFECT OF INTEGRATED NUTRIENT MANAGEMENT ON NITROGEN UPTAKE IN RICE-NO TILL JOWAR CROPPING SEQUENCE - B. MOUNIKA (The Journal of Research ANGRAU, 2018)
The experiment was conducted during Rabi for two consecutive years (2015-2016 and 2016-2017) on sandy clay loam soils. The treatments consisted of different combinations of nitrogen during kharif preceding rice crop and three nitrogen levels applied during rabi no till jowar crop. The experiment was laid out in a split plot design with thirteen main plots (preceding kharif rice) split into three sub plots (rabi no till jowar), thus, total 39 treatments and replicated thrice. Results indicated that all the characters studied were significantly higher with application of 100% RDN through inorganic fertilizer (T1) during kharif and 100% N level applied during rabi however it was on a par with that of application of 50% RDN+ 50 % Green manure (T12), 50% RDN + 50% Poultry manure (T6) and 100 % N level during rabi in both the years of study.